Review of organic corrosion inhibitors: application with respect to the main functional group - Darya Puzikova; Gulinur Khussurova; Xeniya Leontyeva; Oleg Kholkin; Nail Kenzin; Murat Zhurinov; Svetlana Peshaya (Journal of Saudi Chemical Society)
Abstract Corrosion remains a significant challenge in the oil and gas industry, adversely impacting all stages of the production cycle, including exploration, extraction, transportation, and refining. This review provides a comprehensive analysis of corrosion mechanisms, classification systems, and the practical application of corrosion inhibitors, with particular emphasis on their effectiveness in protecting oilfield and refinery equipment. Special attention is given to organic corrosion inhibitors, specifically those based on imidazolines, phosphonates, and urotropine. These compounds are known for their ability to form protective films that reduce corrosion rates in harsh environments characterized by high concentrations of H2S, CO2, and other aggressive agents. Imidazoline-based inhibitors are recognized for their capacity to establish hydrophobic barriers on metal surfaces, while phosphonates are particularly effective under high-temperature conditions. Urotropine, in turn, demonstrates considerable efficiency in acidizing operations commonly employed in well stimulation. The review also explores the synergistic effects achieved through the combined use of different corrosion inhibitors, resulting in improved overall protection. In addition, it addresses critical challenges such as the environmental impact and toxicity of certain conventional inhibitors, underscoring the urgent need for the development of sustainable and environmentally friendly alternatives. This analysis aims to support the optimization of corrosion control strategies, thereby enhancing operational reliability and extending the service life of vital infrastructure in the oil and gas sector.